HUBUNGAN HASIL SUPPLEMENTARY SCALES MMPI-2 TERHADAP HASIL UJI KOMPETENSI PADA ALUMNI KEBIDANAN MAKASSAR PERIODE MARET TAHUN 2018 - Yuliati Yuliati; Saidah Syamsuddin; Budu Budu (Universitas Muhammadiyah Tangerang, 2020)
Various government efforts to reduce Maternal Mortality Rate (MMR), Infant Mortality Rate (IMR), and Under-Five Mortality Rate (UFMR) have been carried out through the Maternal and Child Health program. The research aimed to investigate the relationship between MMPI-2 Supplementary Scales Result and Competency Test Result on Makassar Midwifery Alumni in the Period of March 2018.The research used the observational descriptive method with the cross sectional study design. The research population was all midwifery alumni Health Higher School Mega Rezky Makassar and Midwifery Academy Yapma who attended the competency test in the period of March 2018. Samples were selected using the consecutive sampling technique. The samples were as many as 122 respondents who were divided into two groups namely 61 competent and 61 incompetent respondents. Data were collected MMPI-2 test questionnaire distributed to the respondents and examined by experts. The data analysis used the Chi-square test.The research result of the Supplementary scales distribution indicates the significant scales namely : the Anxiety (A),Ego Strength (ES), Responsibility (Re), Post Traumatic Disorder Keane (PK), and Addiction Admission Scale (AAS). This proves that there is the relationship between MMPI-2 Supplementary Scales Result and competency test result. Key words : Supplementary Scales, Midwifery Alumni, Competency Test.